Development of Media Literacy as a Key Requirement of the European Union - Danail Danov (Проблеми на постмодерността, 2019)
This article traces the key documents of the European Union related to the media literacy development. Along with that it offers a new and more extended understanding of the very concept due to the rapid dynamics of the interaction of various political, technological and socio-cultural factors. The article is a part of an in-depth research offering a self-sustainable model for media literacy development in Bulgaria.